A teaching experience in problem solving maritime school mathematics teachers' account - Fojas, Rudy L.
This study investigates the lived experiences of mathematics teachers in a maritime school, focusing on their roles in teaching problem solving and how the maritime educational context influences their strategeies and professional growth. guided by Situated Learning theory, the research explores the contributions of communities of practice in enhancing problem-solving skills among students and fostering collaborative professional development. Employing a qualitative phenomenological design, the study was conducted at John B. Lacson Foundation Maritime University (Molo), Inc. Three mathematics teachers were purposively selected for in-depth interviews, which were transcribed, validated, and analyzed thematically. The analysis revealed four key themes: Teaching in Context,Fostering Collaboration, Using Appropriate Scaffolding, and Growing Professionally. The findings underscore the significance of integrating maritime-specific examples and practical applications into problem-solving instruction. teachers leveraged scaffolding, technology, and collaborative learning to enhance engagement and effectiveness. Communities of practice played a pivotal role in addressing challenges, sharing resources, and promoting continuous improvement through workshops and peer mentoring. The study concludes that adapting teaching practices to the maritime context enriches problem-solving instruction and prepares students for industry demands. It highlights the importance of professional collaboration in overcoming challenges and advancing instructional practices. These insights contribute to refining mathematics education in maritime schools and encourage future research to expand n student perspectives and other maritime institutions.